THE ROLE OF THEATRES(PLAYHOUSES) DURING THE RENAISSANCE PERIOD - Narxadjayeva Madina Abduvali qizi, Scientific adviser: Khamitov Eldorbek Erkinovich (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
During the Renaissance period, theatres, also known as playhouses, played a pivotal role in shaping cultural, social, and intellectual life. They served as centers for artistic expression, showcasing the works of playwrights such as Shakespeare, Marlowe, and Ben Jonson. Renaissance theatres promoted literacy, education, and moral reflection by dramatizing historical events, classical myths, and contemporary issues. Playhouses also functioned as social spaces where people from different classes interacted, fostering community engagement and shared cultural experiences. Architecturally, theatres like The Globe and The Rose reflected innovative designs that enhanced audience visibility and acoustics. Moreover, they contributed to the professionalization of acting and theatrical production, influencing European theatre traditions for centuries. Overall, Renaissance playhouses were not merely entertainment venues but vital instruments for intellectual growth and cultural identity.